Feminist social thought : An introduction to six key thinkers - Bhagwat, Vidyut (New Delhi : Rawat Publications, 2024)
Feminist Social Thought gives a real insight into the works of six noteworthy feminist thinkers, namely, Simone de Beauvoir, Betty Friedan, Kate Millett, Shulamith Firestone, Juliet Mitchell and Sheila Rowbotham. The text promises to be the much-needed handbook for teachers and students of feminist thought giving a clear understanding of the classics of second wave feminism. This book offers a comprehensive and coherent guide to second wave feminist thinkers for students of Women's Studies, Sociology, and Social and Literary Theory.
Keywords: Feminist ethics; Social Science / Feminism & Feminist Theory; Social Science / Gender Studies; Social Science / Women's Studies; Women -- Social conditions; Feminist theory